(3GdeGd hGdgdGd (B:s (3GdehGfY hGdOhGaY GdEbJUGOjI dXghQ GdESdGe (B/s - (3GdfGHdSj, TGcQs ((3HjQhJ(B: s (3OGQ GdSGbj(B, s, 2002)
(3eGd GdYQH bHd GdESdGe(B- (3GdehGfY GdEbJUGOjI dXghQ GdESdGe , OhQ GdjghOjI hGdeSjMjI hGdMfjajI hGdUGFHI aj XghQ GdESdGe, GdOhGaY GdEbJUGOjI dXghQ GdESdGe, GdaJM HOdG ef GdJLGQI, eGd GdYQH HYO GdESdGes
(3GdeQGLY U(B.185 (3GdagQS GdJMdjdj U(B.193s
Keywords: (3GdEbJUGO GdESdGejs; (3GdJLGQIs; (3GdeGds